Complexity hints for economic policy - Salzano, Massimo. (Springer)
General issues - rationality, learning and complexity: from the homo economicus to the homo sapiens - The confused state of complexity economics: an ontological explanation - Modeling issues I: modeling economic complexity - The complex problem of modeling economic complexity - Visual recurrence analysis: application to economic time series - Complexity of out-of-equilibrium play in tax evasion game - Modeling issues II: using models from physics to understand economicphenomena - A new stochastic framework for macroeconomics: some illustrative examples - Probability of traffic violations and risk of crime: a model of economic agent behavior - Markov nets and the netlab platform: application to continuous double auction - Synchronization in coupled and free chaotic systems - Agent based models - Explaining social and economic phenomena by models with low or zero cognition agents - Information and cooperation in a simulated labor market: a computational model for the evolution of workers and firms - Applications - income inequality, corruption, and the non-observed economy: a global perspective - Forecasting inflation with forecast combinations: using neural networks in policy - Policy issues - the impossibility of an effective theory of policy in a complex economy - Implications of scaling laws for policy-makers - Robust control and monetary policy delegation.